2017
DOI: 10.4236/ojst.2017.78030
|View full text |Cite
|
Sign up to set email alerts
|

One Case of Root Tip Foreign Body of Anterior Tooth Trauma

Abstract: Patients with obsolete anterior tooth trauma often see a doctor because of dental stain or gingiva tumefaction and suppuration in clinical. In this case, a 28-year-old female patient took root canal therapy for repeated gingiva tumefaction and tooth stain in anterior teeth of left maxillary and giant foreign body at apex shown in X-ray photography. After removing the foreign body at apex by endodontic surgery, internal bleaching and resin repair were conducted. The therapy shows that the usage specification of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In clinical practice, some scholars [26][27] have confirmed that fiberband composite resin splint has a good effect on gingival index, plaque index, gingival crevicular bleeding, and the imaging examination of postoperative two-year follow-up. Zhu Wenting et al [28] found in the clinical observation of 320 cases of permanent anterior teeth that fiber composite resin has strong aesthetics and comfort, is easy to maintain good oral hygiene, and can ensure high bonding strength even if the adjacent teeth of the affected teeth are primary teeth. In addition, the operation time of fiber composite resin splint in the patient's mouth is short, and it is more suitable to be used for post-traumatic examination and treatment of children in a state of fear [29] .…”
Section: Elastic Fiber Composite Resin Splintmentioning
confidence: 99%
“…In clinical practice, some scholars [26][27] have confirmed that fiberband composite resin splint has a good effect on gingival index, plaque index, gingival crevicular bleeding, and the imaging examination of postoperative two-year follow-up. Zhu Wenting et al [28] found in the clinical observation of 320 cases of permanent anterior teeth that fiber composite resin has strong aesthetics and comfort, is easy to maintain good oral hygiene, and can ensure high bonding strength even if the adjacent teeth of the affected teeth are primary teeth. In addition, the operation time of fiber composite resin splint in the patient's mouth is short, and it is more suitable to be used for post-traumatic examination and treatment of children in a state of fear [29] .…”
Section: Elastic Fiber Composite Resin Splintmentioning
confidence: 99%